2021
DOI: 10.3390/jcdd8080098
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fibrillogenesis in the Mitral Valve: It’s a Matter of Compliance

Abstract: Collagen fibers are essential structural components of mitral valve leaflets, their tension apparatus (chordae tendineae), and the associated papillary muscles. Excess or lack of collagen fibers in the extracellular matrix (ECM) in any of these structures can adversely affect mitral valve function. The organization of collagen fibers provides a sophisticated framework that allows for unidirectional blood flow during the precise opening and closing of this vital heart valve. Although numerous ECM molecules are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…27 This finding supports the observed decreased valve thickness in MAZ51-treated valves as it is known that valve thickening is partially due to increased collagen production. 24,28 Indeed, we found that the area of positive collagen staining decreased only in MAZ51-treated valves (Figure S12D) and collagen area significantly correlated with valve thickness (Figure S12E). These findings demonstrate that VEGF-C-VEGFR3 signaling is important for the growth and/or maintenance of lymphatic vessels in the inflamed valve during peak inflammation, but loss of these lymphatics during that time frame does not directly affect valve disease progression.…”
Section: Vegf-c-vegfr3 Signaling Regulates Lymphatic Outgrowth In The...mentioning
confidence: 88%
“…27 This finding supports the observed decreased valve thickness in MAZ51-treated valves as it is known that valve thickening is partially due to increased collagen production. 24,28 Indeed, we found that the area of positive collagen staining decreased only in MAZ51-treated valves (Figure S12D) and collagen area significantly correlated with valve thickness (Figure S12E). These findings demonstrate that VEGF-C-VEGFR3 signaling is important for the growth and/or maintenance of lymphatic vessels in the inflamed valve during peak inflammation, but loss of these lymphatics during that time frame does not directly affect valve disease progression.…”
Section: Vegf-c-vegfr3 Signaling Regulates Lymphatic Outgrowth In The...mentioning
confidence: 88%
“…Collagen fibers are the main contributor to the structural integrity and mechanical competency of MVL 17 19 . In DMVD, MVL is associated with a disrupted microstructure of collagen fibers 8 , 12 , 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the components of the extracellular matrix, collagen is the most important as it is the main mechanical contributor to the proper functioning of mitral valve leaflets (MVL) 17 19 . A disruption of the collagen network leads to significantly altered biomechanics and consequently malfunction of the mitral valve leaflet.…”
Section: Introductionmentioning
confidence: 99%